2006
DOI: 10.5194/angeo-24-3071-2006
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of merging at the magnetopause inferred from dayside 557.7-nm all-sky images: IMF drivers of poleward moving auroral forms

Abstract: Abstract. We combine in situ measurements from Cluster with high-resolution 557.7 nm all-sky images from South Pole to investigate the spatial and temporal evolution of merging on the dayside magnetopause.Variations of 557.7 nm emissions were observed at a 6 s cadence at South Pole on 29 April 2003 while significant changes in the Interplanetary Magnetic Field (IMF) clock angle were reaching the magnetopause. Electrons energized at merging sites are the probable sources for 557.7 nm cusp emissions. At the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…When a solar wind pressure increase occurs, the magnetopause position must move inward to maintain pressure balance. The removal, or erosion, of the magnetic flux between the old and new positions is accomplished by merging [e.g., Siscoe et al , 2002; Maynard et al , 2006; Ober et al , 2007]. The timing of the initiation of these changes is determined by the arrival of the fast shock generated when the solar wind pressure increase crossed the bow shock.…”
Section: Discussionmentioning
confidence: 99%
“…When a solar wind pressure increase occurs, the magnetopause position must move inward to maintain pressure balance. The removal, or erosion, of the magnetic flux between the old and new positions is accomplished by merging [e.g., Siscoe et al , 2002; Maynard et al , 2006; Ober et al , 2007]. The timing of the initiation of these changes is determined by the arrival of the fast shock generated when the solar wind pressure increase crossed the bow shock.…”
Section: Discussionmentioning
confidence: 99%
“…However, the bursty nature of the accelerated ions indicates that intervals of merging occurred, each lasting <1 min. Maynard et al [2004b, 2006] used 557.7 nm observations of the dayside cusp to show that merging events at the magnetopause last from 30 s to a several minutes at any given spot. Such short intervals usually lack enough points to provide significant statistical results.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely in nature that any compression of the magnetosphere during conditions of southward IMF must be transient and in time removed by erosion. In an investigation of the dayside auroral response to small changes in solar wind dynamic pressure, Maynard et al [2006] concluded that changes in the magnetopause position demanded by dynamic pressure changes were accomplished by merging.…”
Section: Discussionmentioning
confidence: 99%